2010
DOI: 10.1002/chem.200902562
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the First Nonracemic Diquats

Abstract: Three tricyclic diquats with an eight-membered ring were prepared and shown to be the first configurationally stable derivatives of their kind. Resolution was achieved by using chiral hexacoordinated phosphorus BINPHAT and TRISPHAT anions. The diquat cations were obtained in high diastereo- and enantiomeric purity (ee>96% in most cases). X-ray diffraction analysis coupled with circular dichroism (CD) measurements allowed a precise determination of the relative and absolute configuration of the salts. The barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 135 publications
0
8
1
Order By: Relevance
“…In addition, the UV–vis spectrum (Figure S4) lacks an intense, low-energy MLCT band characteristic of the conjugated chromophores 1 – 4 . Unlike recently reported nonracemic diquats containing eight-membered rings, [ 4b ] 4+ appears to be conformationally flexible at room temperature.…”
Section: Resultscontrasting
confidence: 64%
“…In addition, the UV–vis spectrum (Figure S4) lacks an intense, low-energy MLCT band characteristic of the conjugated chromophores 1 – 4 . Unlike recently reported nonracemic diquats containing eight-membered rings, [ 4b ] 4+ appears to be conformationally flexible at room temperature.…”
Section: Resultscontrasting
confidence: 64%
“…More recently, the Lacour group revisited some of these dications (Scheme b), and reported the resolution and determination of racemization barriers. This elegant study found the barriers of the selected example diquats to be relatively low (Δ G ≠ =106–112 kJ mol −1 at 20 °C) …”
Section: Methodsmentioning
confidence: 96%
“…[7] However,t he configurational stability and resolution of the enantiomers were not addressed in theser eports.M ore recently,t he Lacour groupr evisiteds omeo ft hese dications (Scheme 1b), and reportedt he resolution and determination of racemization barriers. [8,9] Non-racemic diquats with comfortably high barriers preventing thermalr acemization even at 150-200 8Cw ill enable av ariety of application studies without being restricted to low temperatures. [8,9] Non-racemic diquats with comfortably high barriers preventing thermalr acemization even at 150-200 8Cw ill enable av ariety of application studies without being restricted to low temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This ambivalent behavior is conceptually interesting and can be used for the development of stereodivergent pathways and subsequent applications. 5,14 Knowing, in ortho-ortho′-bridged biaryls, that eight-membered-ring derivatives are usually more configurationally stable that seven-membered analogues, 15 and that this trend is reinforced by a double tethering, 16 an approach was developed for the construction of doubly bridged biphenyl azocines of type 4 and 5 (Figure 1, bottom). Herein, these derivatives S. Harthong et al…”
mentioning
confidence: 99%